Government Discretion In Creating Legal Products For The People - Perdana, Angga; Hidayati, Hidayati (PALAR (Pakuan Law review), 2025)
AbstractThis study aims to ensure public welfare by granting the state administration the freedom to act independently within its authority. Such freedom becomes crucial, especially when addressing issues that require solutions not explicitly stated in existing laws and regulations, or when governance proves inadequate or unclear. The primary goal of this research is to hold the government accountable for its reasonable actions while providing a warning against potential abuses of power. The research adopts a normative legal method with a common law system approach, utilizing secondary data from primary legal books, secondary legal books, and tertiary legal documents. The study addresses problems related to various forms of power misuse, including government officials acting under the guise of their institutions for personal gain. The findings reveal that Law No. 30 of 2014 on Government Administration provides a framework for government officials to tackle issues encountered in administrative governance while maintaining principles of accountability and transparency. In conclusion, the state administrative court plays a vital role in resolving administrative disputes arising from government actions and decisions. Legal enforcement through this court aims to ensure that government decisions do not harm specific individuals or entities while preserving integrity and accountability in the decision-making process. Keywords: Common Sense, Legal Products, People.